Soccer-Related Injuries in Children and Adults Aged 5 to 49 Years in US Emergency Departments From 2000 to 2012. (July 2015) - Esquivel, Amanda O.; Bruder, Adrienne; Ratkowiak, Kaitlyn; Lemos, Stephen E.
Background: An increase in soccer-related injuries occurred in the United States between 2000 and 2012; however, most studies of soccer-related injuries have only examined the pediatric population and not adults. Hypothesis: The number of soccer injuries is increasing in both the pediatric and adult populations. There are differences in injury types and counts when comparing male and female players within various age groups. Study Design: Descriptive epidemiology study. Level of Evidence: Level 4. Methods: This retrospective analysis surveyed the US Consumer Product Safety Commission's National Electronic Injury Surveillance System (NEISS) database from 2000 to 2012 for soccer-related injuries in children and adults aged 5 to 49 years. Results: From 2000 to 2012, there were an estimated 2, 472, 066 soccer-related injuries among 5- to 49-year-olds; 629, 994 (25.5%) in adults (aged 20-49 years). The overall estimated pediatric injury count increased significantly over the time period ( R 2 = 0.764, P < 0.001). In the 20- to 49-year age range, there was also a significant increase in the estimated number of injuries over the 13-year period, from 41, 292 injuries in 2000 to 55, 743 in 2012 ( R 2 = 0.719, P < 0.001). The estimated injury counts for male players were significantly higher than female players in any given year for all age groups ( P < 0.001). Girls aged 5 to 19 years were more likely to have lower extremity injuries than boys (odds ratio [OR], 1.256; 95% CI, 1.214-1.299; P < 0.001). The most common injuries reported were strain/sprains (33.3%), fractures (23.7%), and contusions and abrasions (17.4%) within the 5- to 49-year age category. In both sexes, strains and sprains were significantly lower among 5- to 19-year-olds in comparison with 20- to 49-year-olds (OR, 0.740; 95% CI, 0.714-0.766; P < 0.001). Conclusion: There are age- and sex-related differences in estimated injury count, body part injured, type of injury, and hospital admissions for soccer. Also, estimated injury count increased over the 2000 to 2012 time period. Clinical Relevance: This study demonstrates that there are differences between pediatric and adult injuries, based on sex, body part, type of injury, and hospital admissions.